Conductivity study on plasticized solid bioelectrolytes cmc-nh¬4br and application in solid-state proton batteries - Ahmad Salihin, Samsudin; M. I. N., Isa (Penerbit Universiti Teknologi Malaysia, 2016)
This paper present the development of plasticized solid bio-electrolytes (PSBs) which has been accomplished by incorporating various composition of plasticizer namely ethylene carbonate (EC) with carboxy methylcellulose doped NH4Br via solution casting method. The plasticized polymer–salt ionic conduction of PSBs has been analyzed by electrical impedance spectroscopy. Plasticization using EC in PSBs system assists the enhancement of NH4Br dissociation and therefore increases the protonation process in the system. The highest ionic conductivity obtained for CMC−NH4Br containing with 25 wt. % NH4Br was achieved at 1.12 x 10-4 Scm-1 and improved to 3.31 x 10-3 Scm-1 when EC was added in PSBs system. The ionic conductivity-temperature for PSBs system was found to obey the Arrhenius relationships where the ionic conductivity increases with temperature. The solid-state proton batteries were assembled with the formation of Zn + ZnSO4.7H2O || highest conducting PSBs system || MnO2 and achieve with a maximum open circuit voltage (OCV) of 1.48 V at room temperature and showed good in rechargeablity performance with more than 10 cycles.